THE VALUE OF RENAL DYSFUNCTION IN PATIENTS WITH ACUTE DECOMPENSATED HEART FAILURE - I.I. Gorda (Bogomolets National Medical University, 2016)
Renal dysfunction has a negative impact on the prognosis in patients with ADHF and associated with increased frequency of combined points as death in hospital + ventricular fibrillation + ventricular tachycardia and death in hospital + cardiogenic shock. Such indicators as CVP and E/E', as well as laboratory markers of kidney damage and heart can be used to assesscongestionin patients with renal dysfunction in ADHF.In a prospective study involving 107 patients with ADHF who were hospitalized in the Alexander clinical hospital of Kyiv in 2013. A survey of patients involved in determining the dynamics of ECG, heart ultrasound, X-rays of the chest cavity and the testimony of standard general clinical and biochemical laboratory tests, and central venous pressure (CVP). In addition, 67 patients were determined following markers of heart failure and kidney damage: NT-proBNP (pg / ml) and NGAL (pg / ml) (ELISA). All patients were divided into two groups according to glomerular filtration rate (GFR) during hospitalization. The first group (with reduced GFR) included 46 patients (mean age 64,8 ± 2,72), which was GFR e" 60 ml / h MDRD. The second group (with preserved GFR) included 61 patients (mean age 55,3 ± 2,32), which was eGFR <60 mL/h MDRD.At discharge, patients with reduced GFR were significantly heavier: patients with NYHA II class was lower (19.7% vs. 50%, p <0,01), and patients with NYHA III and IV significantly more (67, 2% versus 41,3%, p <0,05 and 18,0% against 4,3%, p <0,01 respectively). Comparing E/ E'in both groups turned out that the group he reduced GFR was significantly higher at the time of hospitalization (22,5 ±1,2 vs 17,2 ± 1,1, p <0,01), for 3- day (20,1 ± 1,07 to 14,5 ± 1,05, p <0,01) and at discharge (18,1 ± 0,88 to 12,4 ± 0,77,p <0,01).